2021
DOI: 10.1177/0040517521992353
|View full text |Cite
|
Sign up to set email alerts
|

An integrated framework for supplier selection and performance evaluation for apparel retail industry

Abstract: Supplier evaluation, including supplier selection and performance evaluation, has become a critical issue for apparel retailers within the apparel supply chain dealing with severe competition in the global market. An effective evaluation of suppliers requires considering both the quantitative and qualitative performance aspects and integrating the efficiency measurement. In an attempt to address this issue, this study proposes an integrated framework that can handle supplier selection and overall performance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Numerous engineering applications have contributed through the use of GIS. Researchers have found that the increasing number of criteria, variety of data kinds, and measurement units make it impossible to evaluate criteria in site selection quantitatively and that there are interactions between the criteria (Sarıçam and Yilmaz, 2022). Hence, The GIS-based spatial analytical hierarchy process (SAHP) was employed to generate the weights of the criteria and rank the alternatives utilizing pairwise comparison matrix (Shelar et al, 2022).…”
Section: Land Suitability Analysismentioning
confidence: 99%
“…Numerous engineering applications have contributed through the use of GIS. Researchers have found that the increasing number of criteria, variety of data kinds, and measurement units make it impossible to evaluate criteria in site selection quantitatively and that there are interactions between the criteria (Sarıçam and Yilmaz, 2022). Hence, The GIS-based spatial analytical hierarchy process (SAHP) was employed to generate the weights of the criteria and rank the alternatives utilizing pairwise comparison matrix (Shelar et al, 2022).…”
Section: Land Suitability Analysismentioning
confidence: 99%
“…When applied to an MCDM problem, an AHP technique converts psychological characteristics into mathematical reasoning based on relative significance using hierarchical structures (Lin et al , 2019). AHP is a powerful MCDM tool that has been used in areas such as designing a complex decision-making process that requires optimal distribution of work to subcontractors in a garment factory in Turkey (Bulur and Kayar, 2021); developing an integrated framework incorporating suppliers’ selection and comprehensive evaluation of their overall performance (Sarıçam and Yilmaz, 2021); developing a decision support system (DSS) software for classifying and selecting cotton fibers under all aspects of yarn quality (Majumdar et al , 2010) and for comparing fabrics from three different fibers (regenerated bamboo, polyester and cotton) for mechanical, thermal comfort and moisture properties (Saricam and Erdumlu, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Product price was identified as the most important criterion affecting the supplier selection decision. While assessing the performance of apparel retailers, Sarıçam and Yilmaz (2021) presented the combined application of DEA, AHP and TOPSIS methods. AHP was employed to determine the criteria and sub-criteria weights and the apparel retailers were initially ranked using TOPSIS method.…”
Section: Literature Reviewmentioning
confidence: 99%